Behavior of university students cannot buy smartphones - Ihsan Effendi; Adelina Lubis; Nasib Nasib (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research aims to develop a consumer buying model, especially for underprivileged students, especially during the COVID-19 pandemic, which forces students to buy gadgets for college needs. This research was conducted to find out how students make purchases so far. As a result of these changes, it is necessary to study the variables that affect the purchase of these students. The research was conducted at the University of Muhammadiyah North Sumatra (UMSU; Muhammadiyah University of North Sumatra), Medan Area University (UMA), and the Islamic University of North Sumatra (UISU; Islamic University of North Sumatra), which are located in Medan, Indonesia. This research was conducted using a sample of 215 student respondents who bought a smartphone. This study illustrates that price affects purchase intention and actual purchase, but the ease of use does not influence smartphones.